If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + 4 = 2x + -1r Reorder the terms: 4 + -1x = 2x + -1r Reorder the terms: 4 + -1x = -1r + 2x Solving 4 + -1x = -1r + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 4 + -1x + -2x = -1r + 2x + -2x Combine like terms: -1x + -2x = -3x 4 + -3x = -1r + 2x + -2x Combine like terms: 2x + -2x = 0 4 + -3x = -1r + 0 4 + -3x = -1r Add '-4' to each side of the equation. 4 + -4 + -3x = -4 + -1r Combine like terms: 4 + -4 = 0 0 + -3x = -4 + -1r -3x = -4 + -1r Divide each side by '-3'. x = 1.333333333 + 0.3333333333r Simplifying x = 1.333333333 + 0.3333333333r
| 7x-16=16+5x | | 20y+5=p | | 5n-12=(-3)+4 | | 4x+2*5x+5= | | 14x+40=22x | | 2*(x+10)=4*x | | 25=10x+5 | | 12=-1+1 | | 2(x+10)=4*x | | 37t-25=9t-13 | | 112=6x+4y | | 46=47-1x | | 10(y+3)=40 | | 4-3*-5=Y | | 240+0.15x=357 | | 3(4-5m)-12+(-3m)= | | -4-5y=7 | | 3+6x=6-7x | | 18-3x=-22 | | 43+2x=7x+16 | | 10X-40=-10 | | x^4-5x^3-3x^2+13x+10=0 | | 3x+5=95+6 | | 5z-3=2z+9 | | 5p-3=0 | | [7x-7]+3=4x+1 | | f(x) = 7 ( 10 )x+ 1 | | 4p^2+8p^3=0 | | 8i(7-9i)=0 | | 6+2u=-2 | | 2(2s+2)=2s+2s+4 | | e^3x+7=e^2 |